Design and Development of an e-Learning Project Management System: Modelling and Prototyping - Khaldi, Maha; Erradi, Mohamed (International journal of emerging technologies in learning, 2020)
In this work, based on the results obtained concerning the analysis and the needs of our project which concerns the design and development of an e-Learning project management system, we present the modeling stage with UML. Based on one hand, on two diagrams: class diagram and use case diagram, for static modeling and on the other hand, based on three diagrams: activity diagram, sequence diagram, diagram transition state for dynamic modeling. Finally, we offer examples of models for our project.